2011
DOI: 10.1539/joh.l10034
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Human Serum Proteins to Titanium Dioxide Particles In Vitro

Abstract: Binding of Human Serum Proteins toTitanium Dioxide Particles In Vitro: Mazen S.K. Zaqout, et al. Institute of Industrial Ecological Sciences, University of Occupational and Environmental Health, Japan-Objectives: To determine the capacity of human serum proteins to bind to titanium dioxide (TiO 2 ) particles of different polymorphs and sizes. Methods: TiO 2 particles were mixed with diluted human serum, purified human serum albumin (HSA) or purified human serum gamma-globulin (HGG) solutions. After incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
(37 reference statements)
2
14
0
Order By: Relevance
“…The adsorption of proteins onto TiO 2 NPs has been a subject of several studies. [18][19][20][21][22][23][24] In these studies, the connection between protein adsorption and cellular uptake was not investigated. Previously, we have evaluated the effect of physicochemical characteristics of a panel of TiO 2 NPs on uptake by fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of proteins onto TiO 2 NPs has been a subject of several studies. [18][19][20][21][22][23][24] In these studies, the connection between protein adsorption and cellular uptake was not investigated. Previously, we have evaluated the effect of physicochemical characteristics of a panel of TiO 2 NPs on uptake by fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…While the primary entry of TiO 2 nanoparticles (NPs) is the gastrointestinal tract, there are data indicating that the TiO 2 NPs can bind to abundant serum proteins/protein fractions (Zaqout et al . ) and distribute to various organs, further away from the site of the administration. Indeed, Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the larger particles, approximately 5-15% of E171 and E171 containing foods contain below 100-nm diameter nano-sized TiO 2 particles (Peters et al 2014). While the primary entry of TiO 2 nanoparticles (NPs) is the gastrointestinal tract, there are data indicating that the TiO 2 NPs can bind to abundant serum proteins/protein fractions (Zaqout et al 2011) and distribute to various organs, further away from the site of the administration. Indeed, Wang et al (2007) showed that the orally administered TiO 2 NPs could be detected in the liver, spleen, kidneys and lung tissues.…”
Section: Introductionmentioning
confidence: 99%
“…We have observed that with A549 cells (human pulmonary epithelial type II cells) exposed to TiO 2 NPs for 24 h, LDH activity in the cell culture medium dropped markedly at higher TiO 2 concentrations, even though there was a TiO 2 dose-dependent decrease in cell viability as determined by the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay (unpublished data). Based on our recent data showing that TiO 2 particles bind to several serum proteins [7], we hypothesized that TiO 2 NPs could bind to the LDH protein, which might account for the observed effect of TiO 2 NPs on measured LDH activity, particularly if centrifugation is a step in the assay protocol. To provide insight into this possibility, purified LDH preparations were mixed with TiO 2 NPs, followed by centrifugation to separate the supernatant from the precipitated TiO 2 NPs, and the activity and amount of LDH protein in the supernatant was determined.…”
Section: Introductionmentioning
confidence: 99%